MORB-derived amphibolites in the paleozoic basement of the aluminé igneous-metamorphic complex, Neuquén, Argentina: Decoding its genesis, P-T evolution and pre-andean regional correlations - Urraza, Ivana Alejandra (2019)
Amphibolites included in the metapelitic sequence and as xenoliths in intrusive magmatic rocks outcropping in the southern sector of the Aluminé Igneous-Metamorphic Complex (AIMC), Neuquén, Argentina, are studied in detail in order to determine their origin and their subsequent metamorphic evolution. Field evidence and whole-rock geochemistry indicate that these rocks were derived from a Mid-Ocean Ridge Basalt (MORB)-type protolith, and were accreted as tectonic slices into the metapelitic sequence that mainly formed the basal accretionary prism associated with a pre-Andean SW-NE subduction setting. Phase relationships, geochemistry of mineral assemblages and geothermobarometry indicate the presence of at least two metamorphic events (M1 1.9-3.9kbar, 677-745ºC and M2 6.4kbar, 723ºC) framed in a counterclockwise P-T path, comparable to those previously determined for the metapelitic country-rocks and metatroctolites outcropping in the same sector of the AIMC. Based on regional correlations and the agreement in the petrological, geochemical, geochronological and structural characteristics, we suggest that the MORB-derived Ñorquinco amphibolites and neighboring aluminous metasedimentary basement rocks of the AIMC belong to the eastern prolongation of the Western Series of the Coastal Accretionary Complex of Central Chile in west-central Argentina territory.